Pressure levels in the trochanter area according to repositioning at different degrees of inclination in healthy subjects. - Marfil Gómez, Raquel; García-Mayor, Silvia; Morales-Asencio, José Miguel; Gómez-González, Alberto José; Morilla-Herrera, Juan Carlos; Moya-Suárez, Ana Belén; Aranda-Gallardo, Marta; Rincón-López, Trinidad; Lupiáñez-Pérez, Inmaculada (Elsevier, 2020)
Objectives Patient repositioning is a recommended intervention to prevent or treat pressure ulcers (PUs). One option under consideration is the tailored repositioning according to patient characteristics, but more knowledge is needed on how different repositioning patterns influence on skin pressure. To determine what degree of inclination of the body in bed generates more pressure in the trochanteric region. Additionally, to analyze the influence of factors such as gender, age and anthropometric characteristics in the variations of this pressure. Methods Analytical cross-sectional study. Body Mass Index (BMI), lean mass and fat mass were measured in healthy volunteers subject to different inclinations (90°, 60° and 30°) in right lateral decubitus. Pressure was measured with a capacitive surface. Results In total, 146 subjects were included, of which 45 were men and 101 women. The results showed pressure differences due to the inclination according to gender and anthropometric values, being statistically significant in men at 90° and 60°, and in women at 30°. (hombres 90° p = 0,026, 60° p = 0,049; mujeres 30° p = 0,036) según prueba Brown-Forsythe. Conclusions There are differences in the pressures of the trochanteric zone depending on anthropometric factors and by gender, in different body positions. Obese people exerted a higher pressure in the trochanter area at 30° of body inclination than overweight, normal weight and underweight people, respectively. From the clinical point of view, these findings invite to consider a possible differentiation in the repositioning interventions of the patients, according to gender and BMI, as a preventive strategy for PUs.
https://openpolicyfinder.jisc.ac.uk/id/publication/14144
Keywords: Ulceras por presión; Pressure ulcer; Risk factor; Skin; Patient positioning